Parathyroid adenoma: a case report - Kantharia, Shehnaz R.; Kantharia, Rajesh A.; Reddy, Pradeep K.; Mistry, Yogesh M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
The incidence of primary hyperparathyroidism in India is 2.5/1000 individuals. Primary hyperparathyroidism can be caused by a non-cancerous parathyroid adenoma, hyperplasia or rarely by parathyroid carcinoma. Most of these patients have few or no symptoms. Correct diagnosis can be reached by clinical settings, biochemical and radiological tests and final confirmation by histopathology of the specimen.